Organizational leadership : foundations & practices for Christians - Burns, Jack, 1950- (Downers Grove, Illinois : IVP Academic, an imprint of InterVarsity Press, 2014)
Kingdom leadership does not begin and end at the church door. Christians are called to conduct leadership in government, commerce, schools, neighborhoods, families, para-church ministries and a myriad other contexts. God has given us many gifts, and our responsibility is to be stewards of those gifts, and use them to do the King's work. In that context, this text explores key facets of leadership from a Christian worldview so as to equip people to conduct leadership more authentically than would be possible under alternative paradigms. The book begins with the seldom considered theological foundations of leadership while also tracing the historic roots of management, organization and leadership theories. All of this leads to a robust discussion of five essential challenges and practices--communication, negotiation, decision-making, financial stewardship and personal development. --From publisher's description.
Section 1: Theological foundations for Christian leadership -- Called to lead: how do I know? / Timothy G. Dolan -- Leadership in the context of the Christian worldview / Gayne J. Anacker and John R. Shoup -- Toward a biblical theology of leadership / Rick Langer -- Section 2: Theoretical foundations for Christian leadership -- The leadership river: a metaphor for understanding the historic emergence of leadership theory / John S. (Jack) Burns -- Christian leadership on the sea of comlexity / John S. (Jack) Burns -- Section 3: Key skills and practices in Christian leadership -- Communication in the image of God / Ronald K. Pyle -- Conflict and negotiation / John S. (Jack) Burns -- Decision making: becoming an expert of the process / John R. Shoup and Chris McHorney -- Christian leadership and financial integrity: temptation, transformation and transparency / R. Scott Rodin -- Sustaining the leader / Timothy G. Dolan.
Includes bibliographical references and index.
Keywords: Leadership -- Religious aspects -- Christianity; Christian leadership